(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: The process of structural official promotion can be seen still the employees who are not yet qualified rank is determined, the appropriate position, not yet qualified positions of seniority and experience. In the delivery of information only verbally, so it is still difficult to be accepted and understood by the intended object or the information. The purpose of this study was to determine the Structural Promotion System Implementation at the Regional Secretariat Bitung. Research using qualitative methods. The informants were 10 structural, staff / implementers. Data collection by interview, while data analysis using interactive model analysis techniques. The focus of the study was defined as the implementation of a system of promotion or appointment / placement in a structural position as a civil servant which is already regulated in Government Regulation. Number 13 of 2002 on the appointment of civil servants in structural positions. The results showed: (1) policies (rules) is communicated or disseminated to employees, but not formally. Communication and coordination between the implementing unit managers pretty good. (2) The disposition is consistent implementation of regulations on the promotion system of civil servants in a structural position has been good, but not optimally. (3) implementing human resources policies are adequate, especially in BKD and Agency of office and rank position (Baperjakat). (4) The bureaucratic structure / organization and job descriptions of the functions of the implementers of structural officer promotion system is well defined, in which the selection process and the determination of structural officials conducted by Baperjakat, while the technical and administrative processes implemented BKD. Keywords: Structural Promotion Policy Implementation